2022
DOI: 10.1037/bne0000504
|View full text |Cite
|
Sign up to set email alerts
|

Cortical taste processing evolves through benign taste exposures.

Abstract: Experience impacts learning and perception. Familiarity with stimuli that later become the conditioned stimulus (CS) in a learning paradigm, for instance, reduces the strength of that learning-a fact well documented in studies of conditioned taste aversion (CTA; De la Casa & Lubow, 1995;Lubow, 1973;Lubow & Moore, 1959). Recently, we have demonstrated that even experience with "incidental" (i.e., non-CS) stimuli influences CTA learning: Long Evans rats pre-exposed to salty and/or sour tastes later learn unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 56 publications
(109 reference statements)
2
23
1
Order By: Relevance
“…These results indicate that at least in the population of stable taste-responsive GC cells, neural responses evolve from a pattern of dissimilarity to all novel taste stimuli, to one where stimuli evoking similar behavioral responses elicit similar neural patterns. At first glance, these results seem at odds with a recent physiological study in GC in rats, where 3 days of experience with NaCl, citric acid, and water led to an increase in the distinctness of the neural patterns evoked by these stimuli (Flores et al, 2022). However, stimulus delivery was via IO cannulas, so the specific behaviors evoked by the pair of tastants are inferred -it is possible that the citric acid remains aversive over days to rats, unlike the change seen in mice.…”
Section: Familiarity Alters Gc Taste Codingcontrasting
confidence: 76%
See 4 more Smart Citations
“…These results indicate that at least in the population of stable taste-responsive GC cells, neural responses evolve from a pattern of dissimilarity to all novel taste stimuli, to one where stimuli evoking similar behavioral responses elicit similar neural patterns. At first glance, these results seem at odds with a recent physiological study in GC in rats, where 3 days of experience with NaCl, citric acid, and water led to an increase in the distinctness of the neural patterns evoked by these stimuli (Flores et al, 2022). However, stimulus delivery was via IO cannulas, so the specific behaviors evoked by the pair of tastants are inferred -it is possible that the citric acid remains aversive over days to rats, unlike the change seen in mice.…”
Section: Familiarity Alters Gc Taste Codingcontrasting
confidence: 76%
“…They reported that the average response to the stimulus actually increased as the taste became familiar, although this change was only apparent in the late phase of the response. In contrast, Flores et al (Flores et al, 2022) found no change in overall GC responsiveness with three days of familiarization training with two stimuli and water, but did find changes in how these stimuli were encoded (see below). These studies necessarily focused on the responses of only taste-responsive cells.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations